The failure induced by embedment loss of gravity installed anchors in clay. (15th December 2022) - Yang, Yancheng; Liu, Haixiao
Abstract: The reliability of mooring systems is a critical issue for deepwater floating structures. Gravity installed anchors (GIAs) have been effectively employed in a significant number of mooring systems, whose embedment loss and kinematic behaviors under the cable loading conditions also attract attention to the reliability of the anchors during service. Particularly, the embedment loss of the anchor may result in the failure of the anchor. The present work focuses on systematically investigating the failure state of anchors in clay induced by embedment loss under various complex conditions. A theoretical model for analyzing the comprehensive behaviors of the anchor is constructed, which is validated by previous centrifuge tests and 1g model tests. A rational criterion for determining the state of failure induced by embedment loss is proposed and applied to the analytical results of the theoretical model. The factors that have a substantial impact on embedment loss of the anchors, including the anchor embedment depth, anchor orientation, cable loading angle at the seafloor, soil adhesion factor, soil strength, and cable properties are investigated in the analytical cases. OMNI-Max anchors, being one of the most remarkable GIAs and having complex kinematic behaviors, are selected to reveal the influences of these factors on the failure state of the anchors. Based on the results of numerous analytical cases, the failure surfaces in the three-dimensional spatial data field are presented, which reveal the critical state of the anchor under different conditions. Furthermore, these failure surfaces are stated using a surface function. The function can be used as a simple judgment condition for the state of failure owing to anchor embedment loss. The findings of earlier investigations support the applicability of the surface function. In addition, the promising application of the surface function in practice is highlighted. Highlights: Systematical investigation of the failure induced by embedment loss of GIAs. An efficient theoretical model for analyzing comprehensive behaviors of GIAs. A rational criterion for determining the failure status of GIAs induced by embedment loss. Failure surfaces of GIAs based on numerous analytical data. A convenient failure surface function for different scenarios in engineering practice.